Arguing about the World The Work and Legacy of Meghnad Desai - Kaldor, Mary; Vizard, Polly (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. 'The breadth of Meghnad Desai's research interests is awe-inspiring. Hence it is no surprise to see so many who are at the forefront of their respective areas represented in this volume . . . a real treat.' Sunil Wadhwani, CBE, former member of the Monetary Policy Committee, Bank of England Meghnad Desai's work in the social sciences and his contributions to broader political and intellectual life span more than half a century. His multidisciplinary thinking and commitment to social justice, and his efforts in both the academic and political spheres, have inspired many and have highlighted the urgent need for global reforms. This volume is a celebration of Lord Desai's life and legacy from scholars and thinkers who have shared Desai's interests and who are leading contributors in their fields. The book does justice to the diversity and originality of Desai's thought, engaging with the key themes of his life's work and pointing to their relevance in understanding and tackling the challenges of the future.